2019
DOI: 10.1111/ajpy.12245
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Australian marriage equality postal survey and debate on psychological distress among lesbian, gay, bisexual, transgender, intersex and queer/questioning people and allies

Abstract: Objective: In August 2017, the Australian Government announced a voluntary, non-binding postal survey to seek opinion on the legal recognition of same-sex marriage. The government encouraged public debate on the issue. This study sought to identify impacts of the Australian postal survey and associated marriage equality debate on psychological distress experienced by lesbian, gay, bisexual, transgender, intersex, and queer/questioning (LGBTIQ) people and their allies. Method:LGBTIQ identified people (n = 5,742… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 35 publications
7
29
2
Order By: Relevance
“…We found that exposure to negative campaign messages had a detrimental effect in addition to everyday stress, in agreement with the previous literature (Ecker et al, 2019;Frost & Fingerhut, 2016;Verrelli et al, 2019). However, this detrimental effect did not persist when controlling for known minority stressors (such as everyday discrimination, expectations of rejection and internalized homophobia); we thus provide some clarity on the role of negative campaign messages in the minority stress model, a question that was unaddressed (e.g., Ecker et al, 2019) or only partially addressed (e.g., Rostosky et al, 2009) in the previous literature. Second, we explored the possibility that political participation during the campaign might buffer LGB people from the detrimental effects of negative campaign messages.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that exposure to negative campaign messages had a detrimental effect in addition to everyday stress, in agreement with the previous literature (Ecker et al, 2019;Frost & Fingerhut, 2016;Verrelli et al, 2019). However, this detrimental effect did not persist when controlling for known minority stressors (such as everyday discrimination, expectations of rejection and internalized homophobia); we thus provide some clarity on the role of negative campaign messages in the minority stress model, a question that was unaddressed (e.g., Ecker et al, 2019) or only partially addressed (e.g., Rostosky et al, 2009) in the previous literature. Second, we explored the possibility that political participation during the campaign might buffer LGB people from the detrimental effects of negative campaign messages.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, exposure to negative campaign messages decreased emotional and relational wellbeing in a small sample of American same-sex couples (Frost & Fingerhut, 2016) during a recent wave of state-level marriage referenda. The same effect was found in two large Australian samples during the postal vote campaign we study in this paper (Ecker, Riggle, Rostosky, & Byrnes, 2019;Verrelli, White, Harvey, & Pulciani, 2019). However, we know relatively little about the extent and mechanisms of this effect.…”
Section: Negative Campaign Messagessupporting
confidence: 80%
See 1 more Smart Citation
“…Taken together, these findings are revealing a pattern of sexual minority stress effects on non‐heterosexual individuals. While the effects of debate‐related stress were stronger for LGBTIQ people than for allies (Ecker, Riggle, et al, 2019; Ecker, Rostosky, et al, 2019) and for same‐sex attracted gender diverse individuals than opposite‐sex attracted gender diverse individuals, these studies provides evidence for the impact of sexual minority stress on heterosexual individuals. The second major aim of this article is to add to this literature by conducting an in‐depth qualitative exploration to establish the range of the impacts of the postal survey and the surrounding debate on allies.…”
Section: Stigma‐by‐association: Minority Stress Effects On Alliesmentioning
confidence: 74%
“…A large‐scale study from Australia collected data during the period of the postal survey debate ( n = 7,390) explored the relationship between debate‐specific stress and general psychological distress in a sample of self‐identifying LGBTIQ people (78%) and their allies (22%; Ecker, Riggle, Rostosky, & Byrnes, 2019). They found that debate‐specific stress was the strongest predictor of psychological distress for both the LGBTIQ individuals ( sr 2 = .23) and their allies ( sr 2 = .14) in their sample.…”
Section: Stigma‐by‐association: Minority Stress Effects On Alliesmentioning
confidence: 99%